2020
DOI: 10.1093/infdis/jiz622
|View full text |Cite
|
Sign up to set email alerts
|

The Colonization of Carbapenem-Resistant Klebsiella pneumoniae: Epidemiology, Resistance Mechanisms, and Risk Factors in Patients Admitted to Intensive Care Units in China

Abstract: Background Carbapenem-resistant Klebsiella pneumoniae (CRKP) has become a threat to public health, most notably as a superbug causing nosocomial infections. Patients in the intensive care unit (ICU) are at increased risk of hospital-acquired K pneumoniae infection, especially CRKP. This study was conducted to investigate the frequency of gastrointestinal and nasopharyngeal K pneumoniae colonization and its contribution to infections in ICU patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
73
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 25 publications
7
73
0
1
Order By: Relevance
“…Most of the patients with CRKP infection in this study had an advanced age, long hospital stays, a history of antibiotic treatment and invasive operations or treatments during hospitalization, which have been confirmed as important risk factors for CRKP colonization. 29,30 It was reported that CRKP colonization can increase the risk of subsequent infection. 31 Also, the relatively weak immune function of ICU patients may enhance the invasive ability of pathogens, which can be seen in three patients with bloodstream infection.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the patients with CRKP infection in this study had an advanced age, long hospital stays, a history of antibiotic treatment and invasive operations or treatments during hospitalization, which have been confirmed as important risk factors for CRKP colonization. 29,30 It was reported that CRKP colonization can increase the risk of subsequent infection. 31 Also, the relatively weak immune function of ICU patients may enhance the invasive ability of pathogens, which can be seen in three patients with bloodstream infection.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous recent publications have reported that healthy hosts may be asymptomatically colonized with ESBL-producers, with an overall colonization rate of 14%, which is more than a 5% increase from previous studies; there are important geographical differences in the prevalence. In Asia and Africa, the colonization rate may be as high as 46%, whereas in Europe and the Americas, the colonization rate is lower (3-6% and 2%, respectively), but still significant, with a CTX-M-type ESBL dominance [19,20]. The rate of colonization with carbapenemase-producing Enterobacterales is usually much lower (<10%).…”
Section: Introductionmentioning
confidence: 99%
“…The rate of colonization with carbapenemase-producing Enterobacterales is usually much lower (<10%). Unfortunately, it is also increasing worldwide, with some hotspots, for example, in China, with rates as high as 54% [20]. The import and spread of ESBL-or carbapenemase-producers has been recognized as a serious concern, and the travel to (sub)tropical regions (where colonization rates are known to be high) is a risk factor for acquiring colonization by the abovementioned resistant strains [19,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Carbapenem-resistant K. pneumoniae is emerging as a risk to public health as it causes various nosocomial infections, notably respiratory tract infections. Patients in the ICU are at a bigger risk of hospital-acquired K. pneumoniae infection, particularly infections caused by carbapenem-resistant K. pneumoniae [ 13 ]. Carbapenems, a β-lactam antibiotic, target cells by inhibiting transpeptidases which prevent the synthesis of peptidoglycan, a necessary structural component, leading to cell lysis.…”
Section: Introductionmentioning
confidence: 99%